Gerenciamiento del centro de rehabilitación de discapacitados Dr. Lenin Moreno, de la parroquia El Retiro, del cantón Machala en el periodo 2011 - 2012 - Morocho Granda, Susana Andrea (2013)
The present research work contains valuable information regarding the scope of disability, state policies, programs that are developed for the benefit of these people, their rights and also highlights how the management of social work can improve social conditions and Rehabilitation of persons with disabilities.